MOBILE LEARNING SEBAGAI MEDIA PEMBELAJARAN BAHASA INGGRIS - Andika, Mika (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The rapid development of information and communication technology has penetrated all sectors of life, especially the education sector. its development is even  more rapid than originally estimated. We still remember, a few years ago computers and even cellphones were still expensive and only certain people could afford them. Today, people  from various levels of social economic status use the technology.  In fact, many people cannot escape fromthe technology in their daily lives, especially mobile-based technology. Mobile technology has become a very important tool for human life and has changed the mindset and behavior of humans. The problem is: how can we use mobile-based technology positively, wisely and responsibly, especially in the field of English language learning in both formal and informal environments. Based on that problem. This paper discusses about how should students and teachers used  the mobile technology in both formal and informal environments. So that mobile technology is not used as a communication tool but also as  media  to improve English learning.